Candidacy Transformation as Electability Factor of the Legislative Candidate from Prosperous Justice Party (PKS) in Legislative Election 2004-2019 - Ummah, Siti Muslikhatul; Rivai, Ardian Bakhtiar (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This article discusses candidacy transformation which is previously characterized as inclusive-exclusive to inclusive-pragmatic of Prosperous Justice Party (Partai Keadilan Sejahtera/PKS) in the legislative election. The argument is based on the woman candidacy processes of PKS legislative candidates within different legislative election periods namely 2004, 2009, 2014, and 2019. Based on the collected data, the 2009 General Election is the momentum where the most significant legislative seats are acquired by female candidates compared to the other three legislative elections. That phenomenon is this study’s starting point in this article that explores the factors of PKS woman candidate electability, which are each candidate’s social and political capital. This article's conceptual framework is the narration of male power relation as the effort to win seats for PKS woman legislative candidates, which is obtained from the relation with local elites in their respective areas in the 2019 General Election. In contrast to the three previous general elections, the PKS woman legislative candidate electability was sourced from their political and organizational experience and social network in the society. Through a qualitative case study, this article uses interviews as the primary data source, while related documentation and publication as secondary data.